2011
DOI: 10.1590/s1517-83822011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of cold active amylases and proteases of Streptomyces sp. from Antarctica

Abstract: The aim of this study was to isolate novel enzyme-producing bacteria from vegetation samples from East Antarctica and also to characterize them genetically and biochemically in order to establish their phylogeny. The ability to grow at low temperature and to produce amylases and proteases cold-active was also tested. The results of the 16S rRNA gene sequence analysis showed that the 4 Alga rRNA was 100% identical to the sequences of Streptomyces sp. rRNA from Norway and from the Solomon Islands. The Streptomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Another research from Kafilzadeh and Dehdari (2015) also found the potential of gnus Streptomyces isolated from mangrove sediment in amylase enzyme production. There has been reported research that Streptomyces from wide variety of environments like cold places (Antarctica) or associated with invertebrates were potential for the production of amylase enzyme (Cotarlet et al 2011;Khrisnakumar et al 2015). Research from Babu et al (2018) reported that some Streptomyces species such as Streptomyces coelicoflavus, Streptomyces diastaticus, Streptomyces parvus and Streptomyces champavatii were able to produce hydroliytic enzymes (protease, lipase, amylase, chitinase, pectinase, and ligninase) which further have potential as bioremediator agent in P. monodon culture system by the reduction of BOD level in the cultivation system.…”
Section: Screening Of Amylolytic Activitymentioning
confidence: 99%
“…Another research from Kafilzadeh and Dehdari (2015) also found the potential of gnus Streptomyces isolated from mangrove sediment in amylase enzyme production. There has been reported research that Streptomyces from wide variety of environments like cold places (Antarctica) or associated with invertebrates were potential for the production of amylase enzyme (Cotarlet et al 2011;Khrisnakumar et al 2015). Research from Babu et al (2018) reported that some Streptomyces species such as Streptomyces coelicoflavus, Streptomyces diastaticus, Streptomyces parvus and Streptomyces champavatii were able to produce hydroliytic enzymes (protease, lipase, amylase, chitinase, pectinase, and ligninase) which further have potential as bioremediator agent in P. monodon culture system by the reduction of BOD level in the cultivation system.…”
Section: Screening Of Amylolytic Activitymentioning
confidence: 99%
“…Besides, they have pharmaceutical and nanotechnological applications and can also be used for effluent treatment [13][14][15]. Hydrolytic enzymes such as proteases account for approximately 60% of the world enzyme trade and are used for treating industrial rejects and in the production of pharmaceuticals [16,17].…”
Section: Introductionmentioning
confidence: 99%